Homocysteine levels in patients of type 2 diabetes mellitus with diabetic nephropathy and its clinical implications - Singla, Heena; Panag, KMDS; Batta, Anil; Goyal, Gitanjali (International Journal of Medical Research and Review, 2015)
Introduction: Diabetic nephropathy is one of the most common and serious complications of long standing type 2 diabetes mellitus. Microalbuminuria is a strong predictor of diabetic nephropathy. Homocysteine level plays an important role in pathogenesis of diabetic microvascular complications, particularly diabetic nephropathy. Vitamin B12, Folic acid and Vitamin B6 facilitate homocysteine metabolism. Methods: This case- control study was carried out at a tertiary care centre. Total 150 subjects were enrolled, which included 60 cases of type 2 diabetes with microalbuminuria, 60 cases of type 2 diabetes without microalbuminuria and 30 healthy controls. Besides routine investigations, fasting blood glucose, glycated haemoglobin, and homocysteine levels in serum were measured. All subjects were screened for microalbuminuria. Statistical analysis was done. Results: Homocysteine levels, fasting blood glucose and glycated haemoglobin were significantly higher in patients of type 2 diabetes with microalbuminuria as compared to those without microalbuminuria (p = 0.00, p = 0.01, p = 0.01). Strong positive correlation was observed between the homocysteine levels and degree of microalbuminuria(r = +0.758, p = 0.00), and also between the fasting blood glucose levels and degree of microalbuminuria (r = +0.259, p = 0.02). Conclusions: It would be useful to perform an early screening for raised homocysteine levels and for low vitamin levels in the patients of uncontrolled diabetics. This would help to evaluate the need of folic acid, Vitamin B12 and Vitamin B6 supplements since these supplements can be beneficial for delaying the progress of diabetic nephropathy in these patients.